Compósitos laminares magnetoelétricos aplicados ao sensoriamento de campos magnéticos - Montanher, Diogo Zampieri (2013)
This work was developed for designing and constructing a magnetic field sensor based in the interaction between the magnetic and the electric ordering of the matter, i.e., the Magnetoeletric Effect. In this sense, the sintering and characterization of the materials that form these sensors was performed. The magnetostrictive material was a Heusler alloy (NixMnyGaz) with a chemical composition near to that of the Ni2MnGa compound. The piezoelectric materials were ferroelectric PbZr0,53Ti0,47O3 + 1 wt% Nb (PZT-5A) ceramics and multiferroic (0,6)BiFeO3-(0,4)PbTiO3 + 5 wt% La (BFPT-5L) ceramics. The whole set of characterizations reveal a magnetic field induced strain for the NixMnyGaz alloy at room temperature. PZT-5A ferroelectric ceramics present an extrinsic magnetoelectric effect of 1.4 V/cm.Oe, while BFPT-5L multiferroic ceramics shows an overlap of the intrinsic and extrinsic magnetoelectric effects, resulting in a magnetoelectric response of 7.5 V/cm.Oe. Three laminated composites were mounted (two with NixMnyGaz and PZT-5A, and one with NixMnyGaz and BFPT-5L), and their magnetoelectric properties were investigated in order to verify their potential for constructing magnetoelectric magnetic field sensors. The NixMnyGaz/PZT-5A laminated composite shows an extrinsic magnetoelectric effect greater than that of the NixMnyGaz/BFPT-5L composite. However, the NixMnyGaz/BFPT-5L laminated composite presents a dissimilar behavior, in comparison with those mounted with PZT-5A, due to the overlap of the intrinsic and extrinsic magnetoeletric effects observed in the BFPT-5L ceramic. The NixMnyGaz/PZT-5A laminated composite was employed for constructing a multifunctional magnetoelectric-based sensor. A device able to determine continuous magnetic fields in a range that extends from 78 mOe to 10 kOe was developed. Such device presents a time response of 1.5 ms, enabling the detection of pulsed magnetic field with frequencies up to 667 Hz, and magnetic field amplitudes similar to those obtained in the continuous magnetic field detection mode.